Livability in Historic Urban Quarters Case Study: Walled City of Famagusta - Mousavi, Seyed Nima (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Today livability is one of the main issues throughout the world. In general livability has rolled in three main areas: environmental quality, neighborhood amenity and individual well-being. Generally, the concept of livability involves different aspects of urban life; how well the city works for us, as well as how comfortable and enjoyable our neighborhood and city are. Historic preservation could increase the livability in historic districts. Preservation of historical building and cultural heritage leads to increase livability in the area. Livability has many dimensions and indicators. In this study the physical and functional dimension of livability is examined to measure the livability level in the area, although for complete measurement of livability, the social and environmental dimension has to be measured too. Zone 1 of Walled city of Famagusta is taken as a case study of this research. Due to the lack of appropriate historic preservation and obsolescence, the livability level in the area is questionable. The livability of Zone 1 of Walled city of Famagusta is measured, and some recommendations and suggestions for increasing the level of livability are described. However, before measurement of livability in historic urban quarters, it is necessary to mention about the relation between historic preservation and livability, then the measurement due to these relation will be explained. Keywords: Livability, historic preservation, physical and functional dimension of livability, quality of life, quality of place.

ÖZ: Bugun, yaşanabilirlik en önemli konulardan biridir dünya çapındadir. Genel olarak yaşanabilirlik üç temel alanda rolü vardır: çevre kalitesi, mahalle tatlılık ve bireysel refahı. Genel olarak, yaşanabilirlik kavramının kentsel yaşamın farklı yönlerini içerir; şehir bizim için ne kadar iyi, hem de bizim mahalle ve şehir ne kadar rahat ve keyifli bir ortamdir. Tarihi koruma, tarihi bölgelerde yaşanabilirlik artırabilir. Tarihi bina ve kültürel mirasın korunması yaşanabilirlik artmasına neden oluyor. yaşanabilirlik birçok boyutu ve göstergeler vardır. Bu çalışmada yaşanabilirlik fiziksel ve işlevsel boyut yaşanabilirlik seviyesi ölçmek için incelenmiştir, ama yaşanabilirlik tam ölçümü için sosyal ve çevresel boyutu çok dikkatli ölçülmelidir. Mağusanin Suriçi bölgesi bölge 1, bu araştırmanın bir Örnek olay İncelemesi olarak alınmıştır. Uygun tarihi koruma ve eskime olmaması nedeniyle, bölgedeki yaşanabilirlik seviyesi sorgulanabilir. Mağusa Suriçi bölgesi bölgesi 1 yaşanabilirlik ölçülmüştür, ve bazı öneriler ve yaşanabilirlik düzeyini artırarak yüksek ulaşmak için öneriler açıklanmıştır. Ancak, tarihi kentsel kesimlerde yaşanabilirlik ölçümü önce, bu tarihi koruma ve yaşama gücü arasındaki ilişkiyi bahsetmek gerekir, daha sonra bu ilişki nedeniyle ölçüm açıklanacaktır. Anahtar Kelimeler: yaşanabilirlik, tarihi koruma, yaşanabilirlik fiziksel ve işlevsel boyut, yaşam kalitesi, yeri kalitesi.
Master of Science in Urban Design. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Prof. Dr. Naciye Doratlı.
Keywords: Urban Design; Historic buildings - Sustainability - Conservation and restoration - Famagusta (Cyprus, North); Livability; historic preservation; physical and functional dimension of livability; quality of life; quality of place